The Role of Gender in the Adoption of Innovations in Jebel Marra Area, West Darfur State (University of Khartoum Journal of Agricultural Sciences, 2025)
The main objective of this study was to determine the role ofgender in the adoption of innovations in Jebel Marra area, West DarfurState, Sudan. The study was based on primary data collected through afield survey that covered three localities in Jebel Marra area; namely,Zalingei, Garssela and Mornei. The stratified sample technique was usedfor collecting information by using a questionnaire (120 respondents).The multiple regression analysis revealed that although the respondentswere highly aware of agricultural technology, their rates of adoption werestill below optimum, and male respondents exceeded female respondentsin their rate of adoption. Therefore, the study concluded that West DarfurState government could realize more agricultural output througheducating and training the female farmers in Jebel Marra area.
Keywords: Gender; adoption of innovations; Jebel Mara; Sudan